SAT0622 ROLE OF PREGNANCY IN FLARE AND PROGRESSION INTO DEFINED RHEUMATIC DISEASE IN WOMEN WITH UNDIFFERENTIATED CONNECTIVE TISSUE DISEASE: RESULTS FROM A MONOCENTRIC OBSERVATIONAL COHORT. (June 2019) - Motta, Francesca; Ramoni, Véronique; Caporali, Roberto; Grosso, Vittorio; Vitolo, Barbara; Quaglini, Silvana; Montecucco, Carlomaurizio
Abstract : Background: Patients with Undifferentiated Connective Tissue Disease (UCTD) are at risk of disease worsening and progression into well-defined rheumatic disease over time 1 . Only a few studies 2-3 from small cohorts regarding the role of pregnancy in UCTD outcome are available, with no clear-cut factors associated with the evolution of the disease. Objectives: To evaluate the impact of pregnancy on progression from UCTD into a well-defined rheumatic disease. To analyze the role of UCTD flares during pregnancy, as well as clinical and laboratory features in the evolution of the disease; to compare UCTD evolution in patients with or without pregnancy; to compare UCTD evolution in patients with or without UCTD diagnosis before pregnancy. Methods: We collected clinical data from a rheumatologic outpatient clinic regarding women (aged 18-45) with UCTD, from diagnosis to last follow-up. Pregnant women with a previously undiagnosed UCTD were included using a validated two-steps screening method performed at the 1 st trimester during the gynecological ultrasound evaluation, as previously reported 4 . We compared women with at least one pregnancy to non-pregnant women. Student's t test was applied for unpaired, continuous variables, while chi-square to compare percentages. The rate of progression was compared with Kaplan–Meier estimator and Log-rank test. A Cox regression model was fit to assess the association of flare during pregnancy and of clinical and laboratory features with the evolution of the disease. Results: We retrieved data regarding 152 pregnant and 108 non-pregnant patients, mean age of 32 (±6.71) years. We recorded 201 pregnancies. The progression into well-defined disease was observed in 31 (20.4%) pregnant patients and in 5 (4.6%) non-pregnant patients (p<0.001) (fig.1 ). The most frequent evolution was into SLE (52%) in pregnant UCTD and into SSc (40%) in non pregnant patients. We observed 32 flares during pregnancy, mostly with joints involvement (75% of the cases). Having at least one flare during pregnancy, a history of UCTD-related cytopenia and lower levels of C4 in the 6 months before conception were associated with disease evolution. No differences were found as for disease evolution in pregnant patients with or without a previous UCTD diagnosis. Conclusion: The rate of progression from UCTD into a well-defined rheumatic disease is significantly higher in women who had a pregnancy. Having a history of UCTD-related cytopenia, or lower C4 levels before conception, or at least one flare of UCTD during pregnancy significantly increases the risk of progression. The timing of the diagnosis of UCTD, in respect with the pregnancy, does not change the risk of flare and progression. References: [1] Mosca M, Tani C, Vagnani S, et al. The diagnosis and classification of undifferentiated connective tissue diseases. J Autoimmun. 2014 [2] Mosca M, Neri R, Strigini F, et al. Pregnancy outcome in patients with undifferentiated connective tissue disease: a preliminary study on 25 pregnancies. Lupus 2002 [3] Castellino G, Capucci R, Bernardi S, et al. Pregnancy in patients with undifferentiated connective tissue disease: a prospective case-control study. Lupus 2011 [4] Spinillo A, Beneventi F, Ramoni V, et al. Prevalence and significance of previously undiagnosed rheumatic diseases in pregnancy. Ann Rheum Dis. 2012 Disclosure of Interests: Francesca Motta: None declared, Véronique Ramoni: None declared, Roberto Caporali Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Roche, Genzyme, Lilly, MSD, Pfizer, UCB, Vittorio Grosso: None declared, Barbara Vitolo: None declared, Silvana Quaglini: None declared, Carlomaurizio Montecucco Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Sanofi, Genzyme, Lilly, MSD, Pfizer, UCB